DEVELOPMENT OF SMART BOARD MEDIA ON THE ABILITY TO COUNT ADDITION AND SUBTRACTION MATERIALS IN GRADE II ELEMENTARY SCHOOL STUDENTS - Mumpuni, Fanindia Oktavia; Mulyawati, Ima (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research was conducted because there are still many grade II students experiencing difficulties in Mathematics lessons on addition and subtraction operations involving numbers up to 999. This problem arises when teachers have limitations in learning media and only use theme books as learning resources, causing a lack of numeracy skills in students because the learning process runs without using learning media. The purpose of this study is that researchers want to help students improve their numeracy skills by creating smart board learning media that can meet the criteria and eligibility to be used in Mathematics lessons, addition and subtraction materials up to 999. The method used in research is Research and Development (R & D) using a 4D model which includes the stages of define, design, develop, and disseminate. Experts and grade II students of SDN Nagrak 03 filled out questionnaires that were used to collect data. Participants in this study were grade II students of SDN Nagrak 03, This study was divided into 2 groups, namely a large group of 28 students and a small group of 7 students. Based on the validation results, 95% of the media expert category is valid and very useful, for material experts there are 2 validation results, namely with a 93% validation percentage and a 98% validation percentage, both of which show the valid and very useful expert category. In addition, 93% of small group answers fall into the